Holistic Integration of Islamic Religious Education Values: A Comprehensive Strategy for Character Development at MAN 1 Tapanuli Tengah - Rukmana, Siti; Pasaribu, Munawir; Sofyan, Sofyan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
The increasing complexity of modern challenges, including moral degradation and the influence of digital culture, underscores the need for effective integration of Islamic Religious Education (PAI) values in schools. This study used a descriptive qualitative approach to investigate how PAI values are embedded in MAN 1 Tapanuli Tengah, focusing on teachers, principals, and students' processes, experiences, and perspectives. Data were collected through semi-structured interviews, participatory observation, and document analysis. They were analyzed using Miles and Huberman's interactive model, which includes data reduction, presentation, and conclusion drawing and is validated through triangulation. The findings indicate a holistic framework built on three core components: faith (akidah), worship, and moral behavior (akhlak). Akidah serves as the spiritual foundation, fostering moral clarity and emotional stability. Worship, exemplified through communal prayer and dhikr, fosters spiritual discipline and social harmony. Ethical behavior is reinforced through educational strategies emphasizing honesty, responsibility, and tolerance, creating an environment supporting students to practice these values daily. This implementation involves role modeling from teachers, habituation, persuasive counseling, and educational sanctions to shape students' character and discipline. However, challenges remain due to limited parental involvement, peer influence, and unregulated use of social media. Theoretically, this research expands the role of religious education from mere knowledge transfer to character building. Practically, it provides insights into value-based education strategies by emphasizing collaboration between schools, families, and communities to address the challenges of the digital age. The findings contribute to local and global perspectives in strengthening value-based education.